(untitled) (International Journal of Physiotherapy, 2025)
Background: Falls are common in older adults, and physiotherapy plays a crucial role in preventing falls and minimizing their consequences. The purpose of the study was to forecast future directions in research on the role of physical therapy in preventing falls among older people, to thoroughly identify collaboration networks, to monitor research trends, and to highlight current hotspots. Methods: Research about the role of physiotherapy in fall prevention in the geriatric population published in the PubMed Database from January 01, 2005, to June 02, 2025, was retrieved. The bibliometric analysis was conducted using RStudio version 4.5.0 (2025–04–11–ucrt) and the Bibliometric and VOSviewer software (version 1.6.20). Results: Australia was found to be the highest productive country with 362 research articles, and the University of Sydney was the most productive institution, with 79 articles. The journal “BMC Geriatrics” (N=50) and Sherrington C (N=21) were the most productive journal and author respectively. Conclusions: At present, “exercise”, “independent living”, “fear”, “exercise therapy”, “physical therapy modalities”, “gait”, “humans”, “aged”, and “accidental falls or prevention and control” are important research topics. Future research from other parts of the world may offer a diverse perspective.